Circular Economic Analysis of Black Soldier Fly Maggot Cultivation as Local Chicken Feed - Namira Sukma Nurindra; Pria Sembada; Ima Kusumanti; Gilang Ayuningtyas; Danang Priyambodo (Jurnal Ilmu Pertanian Indonesia, 2025)
Waste management is still a significant challenge in Indonesia; organic waste is the most abundant type of waste on a national scale. A potential solution to this problem is to utilize black soldier fly (BSF) larvae as a bioconversion agent for organic waste. The purpose of this study is to determine how much organic waste is absorbed by BSF maggots, to determine the financial feasibility of BSF maggots as local chicken feed, and to analyze the efficiency value of BSF maggot cultivation in a circular economic system. The study utilized four distinct growing media: P0 = 100% kitchen organic waste (KOW); P1 = 100% cow dung; P2 = 50% KOW, 50% cow dung; and P3 = 50% KOW, 50% dairy waste. The analysis used in this study is descriptive-quantitative, and economic analysis is carried out by comparing the processes of drying, grinding, and mixing local chicken feed. The total amount of decomposable organic waste is 237 kg. Media grows P3, which is the most profitable for BSF maggot cultivation. Maggot meal production is worth developing based on the payback period and R/C. P1 can help the composting process, and production costs are efficient. The processing of maggot flour into local chicken feed is a lucrative venture, as evidenced by the potential profits it generates. This research underscores the significance of implementing a circular economy with BSF maggots in decomposing organic waste and its utilization as an ingredient in chicken feed. Keywords: BSF larvae, circular economy, organic waste